Synthesis and Stability of Lanthanum Superhydrides. (15th December 2017) - Geballe, Zachary M.; Liu, Hanyu; Mishra, Ajay K.; Ahart, Muhtar; Somayazulu, Maddury; Meng, Yue; Baldini, Maria; Hemley, Russell J.
Abstract: Recent theoretical calculations predict that megabar pressure stabilizes very hydrogen‐rich simple compounds having new clathrate‐like structures and remarkable electronic properties including room‐temperature superconductivity. X‐ray diffraction and optical studies demonstrate that superhydrides of lanthanum can be synthesized with La atoms in an fcc lattice at 170 GPa upon heating to about 1000 K. The results match the predicted cubic metallic phase of LaH10 having cages of thirty‐two hydrogen atoms surrounding each La atom. Upon decompression, the fcc‐based structure undergoes a rhombohedral distortion of the La sublattice. The superhydride phases consist of an atomic hydrogen sublattice with H−H distances of about 1.1 Å, which are close to predictions for solid atomic metallic hydrogen at these pressures. With stability below 200 GPa, the superhydride is thus the closest analogue to solid atomic metallic hydrogen yet to be synthesized and characterized.